A New Measure of Monetary Shocks: Derivation and Implications - Romer, Christina D; Romer, David H (American Economic Review, 2004)
This paper develops a measure of U.S. monetary policy shocks for the period 1969–1996 that is relatively free of endogenous and anticipatory movements. Quantitative and narrative records are used to infer the Federal Reserve's intentions for the federal funds rate around FOMC meetings. This series is regressed on the Federal Reserve's internal forecasts to derive a measure free of systematic responses to information about future developments. Estimates using the new measure indicate that policy has large, relatively rapid, and statistically significant effects on both output and inflation. The effects are substantially stronger and quicker than those obtained using conventional indicators.